Protein Isoaspartate Methyltransferase Is a Multicopy Suppressor of Protein Aggregation in Escherichia coli - Kern, Renee (2005)
We used preS2-S′-β-galactosidase, a three-domain fusion protein that aggregates extensively at 43°C in the cytoplasm of Escherichia coli, to search for multicopy suppressors of protein aggregation and inclusion body formation and took advantage of the known differential solubility of preS2-S′-β-galactosidase at 37 and 43°C to develop a selection procedure for the gene products that would prevent its aggregation in vivo at 43°C. First, we demonstrate that the differential solubility of preS2-S′-β-galactosidase results in a lactose-positive phenotype at 37°C as opposed to a lactose-negative phenotype at 43°C. We searched for multicopy suppressors of preS2-S′-β-galactosidase aggregation by selecting pink lactose-positive colonies on a background of white lactose-negative colonies at 43°C after transformation of bacteria with an E. coli gene bank. We discovered that protein isoaspartate methyltransferase (PIMT) is a multicopy suppressor of preS2-S′-β-galactosidase aggregation at 43°C. Overexpression of PIMT reduces the amount of preS2-S′-β-galactosidase found in inclusion bodies at 43°C and increases its amount in soluble fractions. It reduces the level of isoaspartate formation in preS2-S′-β-galactosidase and increases its thermal stability in E. coli crude extracts without increasing the thermostability of a control protein, citrate synthase, in the same extracts. We could not detect any induction of the heat shock response resulting from PIMT overexpression, as judged from amounts of DnaK and GroEL, which were similar in the PIMT-overproducing and control strains. These results suggest that PIMT might be overburdened in some physiological conditions and that its overproduction may be beneficial in conditions in which protein aggregation occurs, for example, during biotechnological protein overproduction or in protein aggregation diseases.